Radon-Distribution Measurements With CR-39, LR-115 And CN-85 DeteCtors - Mahdi, K. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The aim of this work is to determine radon and its decay product concentratiQns indoor and outdoor in different areas in north and middle areÂ·a of Iraq by using nuclear trak detectors , CR-39 , CN- 85 andLR-115. - For CR-39 detectors , the highest radon concentration was (64.07Bq/m3)indoor and (52.4 Bq/m3) outdoor , in Autumn season . And the concentration of that radon and its decay product indoor were greater than outdoor . temperature seems to playsapredominant role in the formation of radon concentration .